Modified retroperitoneal lymph node dissection for post‐chemotherapy residual tumour: a long‐term update. (11th April 2017) - Cho, Jane S.; Kaimakliotis, Hristos Z.; Cary, Clint; Masterson, Timothy A.; Beck, Stephen; Foster, Richard
Abstract : Objective: To update previously reported outcomes of modified‐template post‐chemotherapy retroperitoneal lymph node dissection (PC‐RPLND) in appropriately selected patients with metastatic non‐seminomatous germ cell tumour (NSGCT), as our previous report was criticised for short follow‐up and so we now provide a long‐term update on this cohort. Patients and Methods: In all, 100 patients with normal serum markers after cisplatin‐based chemotherapy and residual retroperitoneal tumour underwent modified PC‐RPLND between 1991 and 2004. Using a prospectively managed institutional testicular cancer database, long‐term follow‐up was obtained. Results: As previously reported, 43 patients underwent a right‐modified template, 18 patients underwent a full‐left‐modified template, and 39 patients underwent a left‐modified template. The updated long‐term median follow‐up for the entire cohort is 125 months. Seven patients developed recurrent disease with a median (range) time to recurrence of 11 (6–102) months, and one patient died from recurrent disease in the chest 4 years after surgery. All recurrences were outside the boundaries of a full‐bilateral template RPLND, with the most common location of recurrence being the chest. The 5‐ and 10‐year recurrence‐free survival rates were 93% and 92%, respectively. The overall survival at 10 years was 99%. Conclusions: In appropriately selected patients with low‐volume disease before and after chemotherapy, a modified template has durable long‐term efficacy without risk of in‐field recurrences at a median follow‐up of 125 months.